2022
DOI: 10.3390/cells11050910
|View full text |Cite
|
Sign up to set email alerts
|

Altered Plasma Fatty Acid Abundance Is Associated with Cachexia in Treatment-Naïve Pancreatic Cancer

Abstract: Cachexia occurs in up to 80% of pancreatic ductal adenocarcinoma (PDAC) patients and is characterized by unintentional weight loss and tissue wasting. To understand the metabolic changes that occur in PDAC-associated cachexia, we compared the abundance of plasma fatty acids (FAs), measured by gas chromatography, of subjects with treatment-naïve metastatic PDAC with or without cachexia, defined as a loss of > 2% weight and evidence of sarcopenia (n = 43). The abundance of saturated, monounsaturated, and poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…It has been shown that abnormally high LIF expression in the tumor microenvironment can promote macrophage aggregation, which could secrete IL6 and IL-1α to induce muscle atrophy and cachexia [ 61 , 137 ]. It is well known that most patients with advanced PDAC are in a cachectic state [ 138 ], perhaps because LIF is highly expressed in the tumor cells, macrophages, and mast cells in the tumor microenvironment of PDAC patients [ 139 ]. In animal experiments, the removal of macrophages prevented and alleviated cachexia [ 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that abnormally high LIF expression in the tumor microenvironment can promote macrophage aggregation, which could secrete IL6 and IL-1α to induce muscle atrophy and cachexia [ 61 , 137 ]. It is well known that most patients with advanced PDAC are in a cachectic state [ 138 ], perhaps because LIF is highly expressed in the tumor cells, macrophages, and mast cells in the tumor microenvironment of PDAC patients [ 139 ]. In animal experiments, the removal of macrophages prevented and alleviated cachexia [ 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent report indicated that soft tissue changes are initiated in PDAC before skeletal muscle loss ( 19 ), and the significant loss of visceral adipose tissue has been observed in PDAC-CC ( 18 ). In a retrospective cohort study, PDAC-CC was associated with the accumulation of oleic acid in plasma, resulting from malnutritional compensatory mechanisms triggered by the lack of oleic acid uptake into tissue ( 105 ). In a pre-cachexia model, increased FA oxidation occurs before muscle mass reduction, suggesting that FA may serve as a dominant energy source in PDAC-CC ( 18 , 106 ).…”
Section: Eolt Hypothesis In Pdac-ccmentioning
confidence: 99%
“…In KPC and Kras LSLG12D/+ Trp53 f/f mice, adipose tissue browning is associated with increased UCP-1 expression and occurs prior to the onset of fat wasting, consistent with clinical observations ( 108 ). A few studies have suggested that fat loss is an early and precipitating event prior to muscle loss in PDAC-CC, even in the absence of muscle wasting ( 18 , 19 , 21 , 33 , 104 , 105 , 107 ). Clinical studies suggested that fat loss may serve as a driving force for cachexia mortality, emphasizing the important roles of adipocytes in PDAC-CC and supporting the need to monitor adipose in patients with CC ( 20 , 21 ).…”
Section: Eolt Hypothesis In Pdac-ccmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, cachectic cancer patients have both adipose tissue and skeletal muscle wasting ( 61 ). Interestingly, the overall plasma fatty acid levels seem to be maintained and only oleic acid is significantly higher in patients with cachexia ( 62 ).…”
Section: Body Climate: Factors and Components Relevant To Cancermentioning
confidence: 99%